REGIONAL FEATURES OF MEDIUM CITIES’ LOCATION IN UKRAINE - Брацьо, Оксана (Human Geography Journal, 2015)
The medium cities as separate category of urban settlements, their place and value in settlement network are characterized. Regional features of medium cities’ location in Ukraine are explored, their quantitative and demographic characteristics are presented. The valuation of connection between medium cities density and settlement network, demographic and economic indexes is made. The necessity of medium cities’ detailed study is motivated.